GAYA KEPEMIMPINAN, MOTIVASI, BUDAYA ORGANISASI, DAN LINGKUNGAN KERJA BERPENGARUH TERHADAP KINERJA PEGAWAI KECAMATAN DI KABUPATEN BONDOWOSO - Aini, Siti Isriyah Nurul; Widagdo, Suwignyo; Dimyati, Muhaimin (Relawan Jurnal Indonesia, 2023)
The purpose of this study was to examine and analyze the partial and simultaneous influence of leadership style, work motivation, organizational culture and work environment on the performance of sub-district employees in Bondowoso Regency. This research uses an explanatory research approach with a population of 720 employees, and a sample of 144 respondents with the technique of determining the sample is purposive sampling. Data processing was analyzed using descriptive statistics with multiple linear regression analysis techniques using SPSS 22.0. Based on the results of the study, it was concluded that leadership style, work motivation, organizational culture and work environment had a partial or simultaneous influence on the performance of sub-district employees in Bondowoso Regency.